Evaluation of The Arabic Language Learning Program based on The Merdeka Curriculum at a Madrasah Tsanawiyah in Makassar - Nuril Akhyar, Khiyarah; Suhardi, Iwan; Patahuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to evaluate the Arabic language learning program implemented under the Merdeka Curriculum at a Madrasah Tsanawiyah in Makassar, using the CIPP evaluation model (Context, Input, Process, Product). Data were collected through observations and interviews with the Vice Principal for Curriculum Affairs and Arabic language teachers. The data were analyzed qualitatively, drawing on the analytical framework developed by Miles and Huberman. The program’s effectiveness was assessed through the four key components of the CIPP model. The findings reveal that the context aspect – pertaining to program planning – has been achieved in accordance with the established indicators. However, the input dimension indicates that while the school has sufficient capacity to support program implementation, improvements are needed in curriculum development, which should involve more collaborative efforts. The processaspect is rated as moderately effective, although issues remain in time management and in facilitating students’ self-reflection on their ongoing learning needs. The product aspect demonstrates satisfactory learning outcomes; nonetheless, students’ proficiency in Arabic language skills remains relatively low. This is attributed to their diverse educational backgrounds, including those from Madrasah Ibtidaiyah and public elementary schools. These results underscore the need for targeted improvements to enhance the overall effectiveness of the Arabic language learning program within the Merdeka Curriculum framework. Abstrak: Penelitian ini bertujuan untuk mengevaluasi program pembelajaran Bahasa Arab berdasarkan Kurikulum Merdeka di a Madrasah Tsanawiyah Negeri in Makassar dengan menggunakan model evaluasi CIPP (Context, Input, Process, Product). Data dikumpulkan melalui observasi dan wawancara yang ditujukan kepada Wakil Kepala Madrasah bagian kurikulum dan guru Bahasa Arab. Analisis data menggunakan pendekatan kualitatif dengan teori yang dikembangkan oleh Miles dan Huberman. Aspek keberhasilan dievaluasi melalui empat komponen utama model CIPP. Hasil penelitian menunjukkan bahwa aspek context atau perencanaan program telah tercapai sesuai indikator, namun perlu perbaikan dalam penyusunan kurikulum yang seharusnya dilakukan secara tim. Aspek input menunjukkan bahwa kapasitas madrasah mendukung pelaksanaan program. Aspek process dinilai cukup baik, namun masih ditemukan kekurangan dalam pengelolaan waktu dan pelibatan peserta didik dalam refleksi kebutuhan belajar berkelanjutan. Aspek product memperlihatkan hasil yang cukup baik dari sisi nilai pembelajaran, tetapi penguasaan keterampilan berbahasa Arab masih rendah, dipengaruhi oleh latar belakang pendidikan peserta didik yang beragam, baik dari madrasah ibtidaiyah maupun sekolah dasar. Temuan ini menekankan perlunya peningkatan dalam beberapa aspek untuk meningkatkan efektivitas program pembelajaran bahasa arab berdasarkan Kurikulum Merdeka.